What is colitis? Statistical approach to distinguishing clinically important inflammatory change in rectal biopsy specimens. Issue 1 (January 1988) - Jenkins, D; Goodall, A; Drew, K; Scott, B B
Abstract : Measurements of mucosal dimension, architecture, and cell counts in both lamina propria and epithelium were made on rectal biopsy specimens from 20 patients with irritable bowel syndrome ("normal" controls); 54 patients with ulcerative colitis, Crohn's disease, and non-specific proctitis; eight patients with small bowel Crohn's disease; and 34 in whom the rectal biopsy specimen was not diagnostic. Discriminant analysis was applied to multiple variables based on the measurements, and three variables were identified as of high predictive value. The most powerful discriminant was increased lamina propria cellularity in all forms of chronic colitis. The ratios of surface length to mucosal length and of surface epithelial height to crypt epithelial height also emerged as discriminants. Chronic inflammatory bowel disease was distinguished from normal in 95% of cases with a definite pathological diagnosis, and 85% of borderline cases were correctly classified as either normal or inflammatory when judged by the final diagnosis after follow up. This study provides a basis for automated diagnosis of rectal biopsy specimens and provides objectively validated criteria which can also be applied in routine histological diagnosis.